PROTOTIPE MONITORING DAN PENETRALISIR ASAP ROKOK BERBASIS IoT - Basuki, Arif; Erig Efendi; Sudiana; Bagus Gilang Pratama; Septi Savitri (Institut Teknologi Nasional Yogyakarta, 2022)
ABSTRACT The dangers of cigarette smoke are not only harmful to smokers themselves but also to others. Cigarette smoke released from the mouth of smokers has a bad effect on the health of the person who inhales it, in this case, passive smokers. The research tool is a prototype monitoring and neutralizing cigarette smoke based on IoT using the NodeMCU ESP8266 microcontroller as a control center, using the MQ-2 sensor, DHT-11 sensor, DC fan, dot matrix P10, speakers and other materials used in the prototype for neutralizing cigarette smoke. This prototype is designed with the layout and components used to function as much as possible with a suitable place in the room. This research begins by reading the state of the room sending data from the ESP sender to the ESP receiver with the Blynk application communication to be processed from reading to neutralization. The integration of all components in this prototype will result in comfortable room conditions and avoid excessive cigarette smoke.. Keywords: NodeMCU ESP8266, MQ-2, DHT-11, dot matrix P10, Blynk.